A new comprehensive diabetes health literacy scale: Development and psychometric evaluation. (December 2018) - Lee, Eun-Hyun; Lee, Young Whee; Lee, Kwan-Woo; Nam, Moonsuk; Kim, So Hun
Abstract: Background: The prevalence of diabetes is close to reaching an epidemic level, and health literacy has recently emerged as a concept that can influence the health outcomes of patients with diabetes. Health literacy was once defined from the perspective of basic reading and understanding skills, but this has now become more comprehensive to include the abilities and skills to assess, understand, appraise, communicate, and use health information. Nevertheless, there is no instrument reflecting the comprehensive health literacy relevant to diabetes. Objectives: The aims of this study were to develop a comprehensive Diabetes Health Literacy Scale and to evaluate its psychometric properties. Design: An instrument-development study was applied that comprised three steps: conceptualization, item generation and content validity, and field testing of the psychometric properties. Settings: A convenience sample of 462 participants was recruited from December 2016 to September of 2017 at outpatient clinics in 2 Korean university hospitals. Participants: The inclusion criteria for participants were being aged at least 19 years, articulate in the Korean language, and diagnosed with diabetes, while the presence of gestational diabetes was applied as an exclusion criterion. Approximately half of the participants were female (51.1%). The participants were aged 54.5 (SD, 11.0) years, 67.1% of them were taking an oral hypoglycemic agent, and 21.9% of them had well-controlled blood-glucose levels. Methods: The content validity, factorial structure validity, convergent validity, criterion validity, internal consistent reliability, and test–retest reliability of the Diabetes Health Literacy Scale were evaluated. Data were analyzed using exploratory and confirmatory factor analyses, Pearson's correlation, Cronbach's alpha, and the intraclass correlation coefficient. Results: The content validity was assessed by five experts. Exploratory and confirmatory factor analyses yielded a three-factor solution. Convergent validity was demonstrated using measures of diabetes knowledge and self-efficacy. Criterion validity was demonstrated with generic health-literacy questions. Internal consistency reliability and test–retest reliability were found to be acceptable, as indicated by a Cronbach's alpha of 0.91 and an intraclass correlation coefficient of 0.89, respectively. Conclusions: The Diabetes Health Literacy Scale is a new instrument that measures comprehensive aspects of informational, numeracy, and communicative health literacy. It is a short instrument, comprising only 14 items scored on a 5-point Likert scale. The instrument exhibits good psychometric properties for four validity metrics (content, structural, convergent, and criterion validity) and two reliability metrics (internal consistency and test–retest reliability). These findings indicate that the instrument can be applied in both research and clinical practice.